Implementation of One Month One Hadith in Daily Activities at Muhammadiyah Elementary Schools 1 and 2 Sepanjang Sidoarjo - Nazahah Ulin Nuha; Romelah; M. Nurul Humaidi (al-Afkar, Journal For Islamic Studies, 2024)
This study investigates the implementation of the "One Month One Hadits" program at Muhammadiyah 1 and 2 Sepanjang Elementary Schools, Sidoarjo. The program aims to build students' Islamic character by introducing and studying one Hadits of the Prophet Muhammad every month.SD Muhammadiyah 1 and 2 Sepajang designed this program as an effort to strengthen the foundation of children's character, integrating Islamic values in daily activities. Qualitative research methods were used, with primary data from interviews and secondary data from documents. The implementation of the program involves the recitation of Hadits every morning and afternoon, followed by guidance for students to apply it in their daily lives. The program is in line with Muhammadiyah's vision of education, emphasizing character building, Muslim personality, and resilient Muhammadiyah cadres. Students not only memorize the Hadits, but also integrate it in their daily positive behavior. Challenges in implementation involve the resistance of some teachers, which requires better understanding and commitment. The school overcame this by holding regular studies to deepen the program materials, create a common understanding and support the integration of religious values in the school culture. Overall, "One Month One Haditst" at SD Muhammadiyah 1 and 2 Sepanjang is not just a learning routine, but a call to translate religious values into real action. This program not only stimulates intellectual growth, but also forms obedient, responsible and ethical individuals in society.